Study Protocol for Evaluation of an Extended Maintenance Intervention on Life Satisfaction and BMI Among 7–14-Year-Old Children Following a Stay at a Residential Health Camp in Denmark - Kristoffersen, Mette Juul; Michelsen, Susan Ishøy; Rasmussen, Mette; Due, Pernille; Thygesen, Lau Caspar; Krølner, Rikke Fredenslund (Frontiers in Public Health, 2021)
Background: It is challenging to maintain effects of public health interventions. For residential health camps benefits often disappear as the child returns home. Furthermore, long-term effects are often not measured or reported. This paper presents the study protocol for an evaluation of an extended maintenance intervention offered to children who have completed a 10-week residential health camp at one of the five Danish Christmas Seal Houses (DCSH). The target group of DSCH is 7–14-year-olds with social, mental, and/or overweight issues and the overall aim of the camp is to increase life satisfaction and a healthy lifestyle. The primary aim of this study is to assess the effectiveness of the maintenance intervention on children's life satisfaction (primary outcome) and BMI Z-score (secondary outcome) 1 year after health camp. Methods: The extended maintenance intervention is developed by DCSH and delivered to each child and family individually by an intervention coordinator to help children maintain positive benefits of the health camp on life satisfaction and health behaviors after returning to their homes. Intervention activities target the child and the family. The effect will be tested in a quasi-experimental design: The intervention is offered to half of the children at one of the five DSCH (intervention group, N~144) while the other half and the children at the other four DSCH receive a standard maintenance intervention (control group, N~894). Children will complete questionnaires on life satisfaction measured by an adapted version of the Cantril ladder and height and weight prior to health camp, at the end of health camp, 3 months and 1 year after the end of health camp. To enable per protocol analysis and nuanced interpretation of effect estimates, we will monitor the implementation of the intervention by a process evaluation study among children, parents, and follow up coordinators using qualitative and quantitative methods. Discussion: We present a systematic approach to evaluating practice-based interventions in a research design. The study will provide new knowledge on the effectiveness of individualized maintenance interventions on long-term effects on life satisfaction and weight loss among children. Trial registration: Prospectively registered at Current Controlled Trials ISRCTN 13011465 https://www.isrctn.com/ISRCTN13011465